Glossopharyngeal Neuralgia: Epidemiology, Risk factors, Pathophysiology, Differential diagnosis, and Treatment Options - Andrew Han; Carver Montgomery; Alexandra Zamora; Emilie Winder; Adam D. Kaye; Caroline Carroll; Alfonso Aquino; Juyeon Kakazu; Alan D. Kaye (Health Psychology Research)
# Purpose of Review